Synthesis and Characterization of Half‐Sandwich Ruthenium Complexes Containing Aromatic Sulfonamides Bearing Pyridinyl Rings: Catalysts for Transfer Hydrogenation of Acetophenone Derivatives. Issue 18 (14th May 2013) - Dayan, Serkan; Ozpozan Kalaycioglu, Nilgun; Daran, Jean‐Claude; Labande, Agnès; Poli, Rinaldo
Abstract: N ‐(Quinoline‐8‐yl‐aryl)benzenesulfonamides1 –6 were successfully synthesized by the reaction of 8‐aminoquinoline and various benzenesulfonyl chlorides. Then, half‐sandwich ruthenium complexes7 –12 were prepared from the reactions of1 –6 with [RuCl2 (p‐cymene)]2 . The synthesized compounds were characterized by NMR and FTIR spectroscopy and elemental analysis, and compounds8 and9 were further analyzed by X‐ray diffraction. The complexes were screened for their efficiency as catalysts in the transfer hydrogenation of acetophenone derivatives to phenylethanols in the presence of KOH with 2‐propanol (as hydrogen source) at 82 °C, and they all showed good activity. Complexes10 and12 were the most active (turnover frequency values: 703 and 734 h –1, respectively). Abstract : A series of new half‐sandwich Ru II complexes containing sulfonamide ligands were synthesized and characterized by NMR and FTIR spectroscopy and elemental analysis, and two of the complexes were further analyzed by X‐ray diffraction. We investigated the catalytic activity of these complexes in the transfer hydrogenation of a few acetophenone derivatives with the use of 2‐propanol in the presence of base.